Giant Photo‐Induced Current Enhancement in a Core–Shell‐Type Quantum‐Dot Thin Film. (29th January 2020) - Shimizu, Sunao; Matsuki, Keiichiro; Miwa, Kazumoto; Braga, Daniele; Ono, Shimpei
Abstract: Photodetectors are key elements in diverse applications such as high‐speed information processing and ultraviolet (UV) ray skin sensors. Low‐dimensional semiconductors, such as quantum dots (QDs) and their hybrid systems, are promising candidates for high‐efficiency and innovative photodetectors, thanks to their unique optoelectronic characteristics and the high tunability of their physical and chemical properties through material design. It is shown that when CdSe/CdS core–shell QDs are employed in field‐effect transistors (FETs), a sensitive photodetection can be obtained by using a solution‐based approach. The transfer characteristics are dramatically changed by UV light irradiation, showing a light‐induced switching between the on/off states of the FET. Surprisingly, the ratio between the photocurrent and the dark current is larger than 10 5 ; this is the highest record of gate‐tunable current enhancement obtained using a FET. It is speculated that this remarkable result is related to the fact that the combination of the CdSe core and the CdS shell forms type‐I band alignment, which effectively confines carriers to the core of the nanocrystal under dark conditions. The prominent optoelectronic effect in QD thin‐film FETs indicates the high potential of nanostructured materials towards multi‐functionalization. Abstract : Giant photo‐induced current enhancement in a core–shell‐type quantum‐dot thin film is demonstrated by fabricating field effect transistors with CdSe/CdS nanocrystals as active channel materials. The ratio of electrical current under light to that in dark is effectively modulated by scanning the gate voltage and changing the thickness of the thin films.